청소년의 디지털 라이프스타일이 메타버스 서비스 이용 여부에 미치는 영향 - 장천우(Tianyu Zhang); 정용국(Yongkuk Chung) (한국콘텐츠학회 논문지, 24(4), 2024)
본 연구는 청소년의 디지털 라이프스타일이 메타버스 서비스 이용여부에 미치는 영향을 살펴보았다. 청소년의 디지털 라이프스타일을 행동(온라인 미디어 활동), 관심(삶의 가치), 의견(능동적 관여) 차원에서 파악하고, 각 차원이 메타버스 서비스 사용여부에 미치는 영향을 확인하였다. 2022 한국 미디어패널 조사에 포함된 중·고등학생 응답자(N=465)를 대상으로 이항 로지스틱 회귀모형을 적용하여 분석을 하였다. 연구 결과에 따르면, 청소년의 OTT서비스와 웹툰/웹소설 이용량이 증가할수록, 화목한 가정에 대한 가치를 중요하게 생각할수록, 능동적 관여가 높을수록 메타버스 이용 확률이 증가하는 것으로 나타났다. 반면에, 흥미롭고 즐거운 삶과 육체적, 정신적 건강에 대한 가치를 중요하게 생각할수록 메타버스 이용 확률이 낮아지는 것으로 나타났다. This study examined the factors influencing the use of metaverse services by Korean adolescents. It simultaneously considered three aspects of digital lifestyle: A (Activities), various online media activities; I (Interests), values deemed important in life; and O (Opinions), active engagement aimed at providing information and expressing opinions. Using data from the 2022 Korean Media Panel Survey, a binary logistic regression model was applied to respondents aged 13 to 19 (N=465). According to the findings, adolescents' use of OTT services and webtoons/web novels showed a positive relationship with the use of metaverse services. Additionally, the value inclination towards a harmonious family positively influenced the use of metaverse services, whereas an interesting and enjoyable life along with physical and mental health showed a negative influence on adolescents' use of metaverse services. Lastly, active engagement, intended for information provision and opinion expression, had a significant impact on the use of metaverse services. KCI Citation Count: 0